Interventions for increasing the use of shared decision making by healthcare professionals - Légaré, France; Adekpedjou, Rhéda; Stacey, Dawn; Turcotte, Stéphane; Kryworuchko, Jennifer; Graham, Ian D; Lyddiatt, Anne; Politi, Mary C; Thomson, Richard; Elwyn, Glyn; Donner-Banzhoff, Norbert (Cochrane database of systematic reviews, 2018)
Shared decision making (SDM) is a process by which a healthcare choice is made by the patient, significant others, or both with one or more healthcare professionals. However, it has not yet been widely adopted in practice. This is the second update of this Cochrane review. To determine the effectiveness of interventions for increasing the use of SDM by healthcare professionals. We considered interventions targeting patients, interventions targeting healthcare professionals, and interventions targeting both. We searched CENTRAL, MEDLINE, Embase and five other databases on 15 June 2017. We also searched two clinical trials registries and proceedings of relevant conferences. We checked reference lists and contacted study authors to identify additional studies. Randomized and non-randomized trials, controlled before-after studies and interrupted time series studies evaluating interventions for increasing the use of SDM in which the primary outcomes were evaluated using observer-based or patient-reported measures. We used standard methodological procedures expected by Cochrane.We used GRADE to assess the certainty of the evidence. We included 87 studies (45,641 patients and 3113 healthcare professionals) conducted mainly in the USA, Germany, Canada and the Netherlands. Risk of bias was high or unclear for protection against contamination, low for differences in the baseline characteristics of patients, and unclear for other domains.Forty-four studies evaluated interventions targeting patients. They included decision aids, patient activation, question prompt lists and training for patients among others and were administered alone (single intervention) or in combination (multifaceted intervention). The certainty of the evidence was very low. It is uncertain if interventions targeting patients when compared with usual care increase SDM whether measured by observation (standardized mean difference (SMD) 0.54, 95% confidence interval (CI) -0.13 to 1.22; 4 studies; N = 424) or reported by patients (SMD 0.32, 95% CI 0.16 to 0.48; 9 studies; N = 1386; risk difference (RD) -0.09, 95% CI -0.19 to 0.01; 6 studies; N = 754), reduce decision regret (SMD -0.10, 95% CI -0.39 to 0.19; 1 study; N = 212), improve physical (SMD 0.00, 95% CI -0.36 to 0.36; 1 study; N = 116) or mental health-related quality of life (QOL) (SMD 0.10, 95% CI -0.26 to 0.46; 1 study; N = 116), affect consultation length (SMD 0.10, 95% CI -0.39 to 0.58; 2 studies; N = 224) or cost (SMD 0.82, 95% CI 0.42 to 1.22; 1 study; N = 105).It is uncertain if interventions targeting patients when compared with interventions of the same type increase SDM whether measured by observation (SMD 0.88, 95% CI 0.39 to 1.37; 3 studies; N = 271) or reported by patients (SMD 0.03, 95% CI -0.18 to 0.24; 11 studies; N = 1906); (RD 0.03, 95% CI -0.02 to 0.08; 10 studies; N = 2272); affect consultation length (SMD -0.65, 95% CI -1.29 to -0.00; 1 study; N = 39) or costs. No data were reported for decision regret, physical or mental health-related QOL.Fifteen studies evaluated interventions targeting healthcare professionals. They included educational meetings, educational material, educational outreach visits and reminders among others. The certainty of evidence is very low. It is uncertain if these interventions when compared with usual care increase SDM whether measured by observation (SMD 0.70, 95% CI 0.21 to 1.19; 6 studies; N = 479) or reported by patients (SMD 0.03, 95% CI -0.15 to 0.20; 5 studies; N = 5772); (RD 0.01, 95%C: -0.03 to 0.06; 2 studies; N = 6303); reduce decision regret (SMD 0.29, 95% CI 0.07 to 0.51; 1 study; N = 326), affect consultation length (SMD 0.51, 95% CI 0.21 to 0.81; 1 study, N = 175), cost (no data available) or physical health-related QOL (SMD 0.16, 95% CI -0.05 to 0.36; 1 study; N = 359). Mental health-related QOL may slightly improve (SMD 0.28, 95% CI 0.07 to 0.49; 1 study, N = 359; low-certainty evidence).It is uncertain if interventions targeting healthcare professionals compared to interventions of the same type increase SDM whether measured by observation (SMD -0.30, 95% CI -1.19 to 0.59; 1 study; N = 20) or reported by patients (SMD 0.24, 95% CI -0.10 to 0.58; 2 studies; N = 1459) as the certainty of the evidence is very low. There was insufficient information to determine the effect on decision regret, physical or mental health-related QOL, consultation length or costs.Twenty-eight studies targeted both patients and healthcare professionals. The interventions used a combination of patient-mediated and healthcare professional directed interventions. Based on low certainty evidence, it is uncertain whether these interventions, when compared with usual care, increase SDM whether measured by observation (SMD 1.10, 95% CI 0.42 to 1.79; 6 studies; N = 1270) or reported by patients (SMD 0.13, 95% CI -0.02 to 0.28; 7 studies; N = 1479); (RD -0.01, 95% CI -0.20 to 0.19; 2 studies; N = 266); improve physical (SMD 0.08, -0.37 to 0.54; 1 study; N = 75) or mental health-related QOL (SMD 0.01, -0.44 to 0.46; 1 study; N = 75), affect consultation length (SMD 3.72, 95% CI 3.44 to 4.01; 1 study; N = 36) or costs (no data available) and may make little or no difference to decision regret (SMD 0.13, 95% CI -0.08 to 0.33; 1 study; low-certainty evidence).It is uncertain whether interventions targeting both patients and healthcare professionals compared to interventions of the same type increase SDM whether measured by observation (SMD -0.29, 95% CI -1.17 to 0.60; 1 study; N = 20); (RD -0.04, 95% CI -0.13 to 0.04; 1 study; N = 134) or reported by patients (SMD 0.00, 95% CI -0.32 to 0.32; 1 study; N = 150 ) as the certainty of the evidence was very low. There was insuffient information to determine the effects on decision regret, physical or mental health-related quality of life, or consultation length or costs. It is uncertain whether any interventions for increasing the use of SDM by healthcare professionals are effective because the certainty of the evidence is low or very low.